Hubungan Koping Spiritual dengan Post Stroke Depression pada Pasien Stroke Iskemik setelah Tiga Bulan Serangan - Fitria Handayani (Holistic Nursing and Health Science, 2019)
Background: The prevalence of Post Stroke Depression (PSD) among ischemic stroke survivor after three months onset is high. PSD is influenced by biological, psychological, and social factors. Spiritual coping was correlated with good mood among chronic illness patient. However, correlation study between spiritual and PSD was not exist. The aim of the study was to examine the correlation between spiritual coping and PSD among ischemic stroke survivor after three months onset.Method: The design of the study was correlational design. There were 68 respondents involved. The inclusion criteria were ischemic stroke after three months onset, no aphasia, no hearing impairment, and the total score of Mini Mental Status Examination (MMSE) was more than 12. The tools were HAMD-GRID 17 (PSD) and Spiritual Coping Questionaire (SCQ). Validation language conducted in two cycles and the test reliability used alpha cronbach (.776). Ethical approval was conducted by ethical committee of Medicine Faculty. The data collection used was survey. The statistical analyze used the Spearman-rho. Results: The results of the study show that demographic characteristic were equal between male and female. The age ranged 51 to 60 was 42.6%, unemployment patient was 61.8%, and the income less than Rp 1,000,000 was 63.2%. Statistical analyses showed that no correlation between spiritual and PSD (r -.155,  p .205). Discussion: Spiritual transformation process is a complex process and diverse among social situation. Transformation in spiritual responses should be gained in advance study to identify the developing of PSD.